Diabetic Foot Ulcers: The Importance of Patient Comorbidity Recognition and Total Contact Casting in Successful Wound Care. Issue 8 (August 2016) - Jagadish, Mayuri; Mcnally, Michael M.; Heidel, R. Eric; Teffeteller, Susan; Arnold, Joshua D.; Freeman, Michael; Stevens, Scott L.; Grandas, Oscar H.; Goldman, Mitchell H.
Diabetic foot ulcers (DFUs) are a major burden on the health-care system. The purpose of this study is to investigate factors affecting the healing rate of DFU in a university wound care center. Records of DFU patients treated between July 2013 and February 2015 were reviewed. Demographics, comorbidities, wound characteristics, and treatment modalities including offloading, hyperbaric oxygen treatment, total contact casting, and bioengineered skin were investigated. All patients underwent weekly debridement regardless of treatment modality. A total of 114 patients ages 18 to 98 comprised the study population. Total contact casting was the only treatment associated with increased healing ( P = 0.02). Smoking ( P = 0.004) and deep vein thrombosis history ( P = 0.001) significantly decreased the likelihood of wound healing. Patients with past vascular event trended toward longer healing times ( P = 0.07). Total contact casting in combination with weekly wound debridement showed benefit in DFU wound healing, whereas patients with a history of deep vein thrombosis and smoking were less likely to heal.